CHEMICAL ELEMENTS IN SOILS OF UST-KAMENOGORSK - G. K. Galyamova (Юг России: экология, развитие, 2014)
The features of the accumulation of copper, zinc, lead and cadmium in the soil of Ust-Kamenogorsk. Soils of different areas of the city are characterized by different levels of pollution. The maps of the diagram of distribution of chemical elements and their associations in the soils of the city.